Sistem informasi E-Fun Library menggunakan metode Rapid Application Development (RAD) - Artanti, Vera (Maliki Interdisciplinary Journal, 2023)
The E-Fun Library Information System is a system that aims to bring innovation in online library management, and to make it easier for the general public, especially students, to love reading. Seen now the level of reading is very low. This system uses the Rapid Application Development (RAD) Method to speed up the development process and allows flexible adjustments according to user needs. The use of the RAD method in developing library information systems is the right choice to overcome this challenge. The result of this project is an E-Fun Library Information System that can improve user experience in accessing and utilizing library resources. Users can easily explore collections, access and interact with libraries online, making libraries more relevant knowledge centers in the digital information age.